PENGGUNAAN COUNTERWEIGHT DAN SOIL NAILING SEBAGAI ALTERNATIF PERKUATAN LERENG SUNGAI GANDONG MAGETAN JAWA TIMUR PASCA LONGSOR - Rina Zusianti; Luthfi Amri Wicaksono; Paksitya Purnama Putra (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The landslide occurred on the slopes of the Gandong Magetan River. The location of the river in the middle of the city caused landslides to almost reach people's homes. Efforts should to be made to improve slope stability so that it is safe against landslides. Slope stability analysis uses the LEM (Limit Equilibrium Method) with the Geoslope program. The results of the analysis of the slope stability of the existing conditions get the value of the safety factor of 0.379. Alternative reinforcement that is planned is the manufacture of counterweight slopes. Planning of counterweight slope embankment as many as 4 levels with a height of 3 m each level. The results of the counterweight slope stability analysis get a safety factor value of 0.507. The critical area is at the top of the slope so that soil nailing reinforcement is added. The results of the counterweight slope stability analysis with soil nailing and gabion reinforcement obtained a safety factor value of 1.507. So that the slope reinforcement plan is safe against landslides.